Legal Dynamics of EU External Relations - Waele, Henri de (Springer, 2017)
Harold Wilson famously remarked that a week is a long time in politics. Law would seem to be different, in that developments dating back several years can still be easily tagged as ‘recent’ by la doctrine. Nevertheless, even in the legal realm, the passing of half a decade will normally entail a vast series of events producing considerable upheavals; and undeniably, in the field of EU external relations law, a lot has happened since the first publication of Layered Global Player in 2011. In particular, the arrival of new judgments, policy developments and scholarly publications called with ever greater urgency for a thorough updating, adjusting and revising. Accumulated experiences in teaching have, moreover, prompted a slight repositioning of this volume, and a measured modification of its outward appearance. With the kind support of the publisher, it is now consciously styled and marketed as an academic textbook rather than a scholarly monograph (a conversion that has helped to slightly bring down its price tag, too). Content-wise, the changes will be equally noticeable in the inclusion of chapter overviews, clarifying boxes and supplementary examples. A careful combing through of the previous manuscript has sought to ensure that the accessibility of the discussions and analyses is not compromised, but instead further enhanced where possible. The temptation to expand the number of chapters was actively resisted. While seemingly justifiable for some domains in light of their topicality (e.g., the Area of Freedom, Security and Justice), the focus continues to lie on what is arguably the ‘general part’ of this sub-domain of EU institutional law. As before, the intention is to offer an advanced introduction; in this regard Goethe’s famous line, in der Beschr€ankung zeigt sich erst der Meister, nails it perfectly. Once the fundamentals are mastered, proficient readers should be able to explore and establish for themselves how the main rules and principles (may be expected to) apply in specific or adjacent fields
Dissecting a Layered Global Player